Preparticipation cardiovascular screening: application of an extended Italian model in Scotland. Issue 2 (20th January 2011) - Hillis, W S; Stewart, K; Burns, M; Kidd, A; MacLean, J; Macintyre, P D
Abstract : Lecture 29 Cardiac death in sport though infrequent (2 cases per 100 000 subject years) is an emotive subject for both the medical and sporting professions as well as for the general public. The principle causes are recognised worldwide and are similar in different countries and in all sports and are secondary to structural and electrophysiological abnormalities some of which are hereditary. The recognition of these conditions has stimulated the development of individual national screening programmes although these are controversial in terms of cost and practicality. (Wheeler et al ; Ann Intern Med 2010;152 :276–86). In the USA, the programme is limited to symptomatic and family history questionnaires and physical examination. The Italian model which is applied to all secondary school sporting participants adds electrocardiography and the option of echocardiogram if deemed appropriate. The application of this system has reduced the incidence of sporting sudden deaths in Italy from cardiomyopathy (Pelliccia et al ; Eur Heart J 2006;27 :2196). The CAYA Project commencing in October 2009 is a cooperative study of the Scottish Government, SFA, and University of Glasgow based at the Sports Medicine Centre at the National Stadium, Hampden Park, Glasgow. This offers cardiovascular screening with questionnaires, physical examination and ECG but with the addition of an echocardiogram in all. Results: 682 subjects aged 15–25 years have been screened with 95% male involvement from football, athletics, swimming, basketball and gymnastics. Questionnaires Symptomatic response: 84 subjects had non-specific symptoms of chest pains dyspnoea or dizziness. 9 subjects had a history of a cardiac murmur. Few medical conditions were reported 2 subjects had ongoing epilepsy 105 subjects had asthma with 27 with on-going treatment. Family history included 64 with cardiac surgery, and 44 with sudden death, usually in grandparents. 18 had a history of arrhythmias including pacemaker or defibrillator insertion. Clinical examination confirmed six specific cardiac murmurs, 92 (13%) had elevated blood pressure >140/90 after two readings. ECGs: Atrial arrhythmias and heart block occurred in 29 subjects respectively. Left ventricular (LV) hypertrophy (Sokoloff criteria) occurred in 256 (38%). QTc prolongation >440 ms occurred in 41 (6%) with IV conduction defects in 76. ST segment abnormalities were reported in 140 with 31 with specific pathological T wave repolarisation (Pelliccia et al ; N Engl J Med 2008;358 :152). Echocardiography: Valvular regurgitation was found in one valve (225), two valves (100), three valves (14) with an echo diagnosis of LV wall thickness of >11 mm in 176 (25%). Muscle thickness >13 mm occurred in the LV septum in 18, in the LV in 1 and in both in 15. 4 had a septal to LV ratio of greater than 1.3/1. Additional structural diagnoses included PDA (3), bicuspid aortic valve (7), PFO with mobile IAS (5), significant ventricular dilatation (4), coarctation (1) and minor anatomical variants (6). Conclusions: From the CAYA study symptom questionnaires have limited returns and the family history returns reflect the disease prevalence in older relatives. The major finding in clinical examination is hypertension. Electrocardiology confirms changes associated with athletic training however may also show changes suggestive of pathology and require further review. Echocardiography confirms changes consistent with athletic training but also reveals unsuspected structural abnormalities requiring additional imaging.